Exploring Stakeholders' Insights into TVET Curriculum in Nepal: A Qualitative Inquiry on Relevance and Practice - Baral, Durga Prasad; Paudel, Lekha Nath (Journal of Technical and Vocational Education and Training, 2025)
This study explores the insights of various stakeholders into the relevance and practice of the Technical and Vocational Education and Training (TVET) curriculum under the Council for Technical Education and Vocational Training (CTEVT) in Nepal. How TVET stakeholders see the existing situation of TVET curricula in Nepal, and how they see the solutions were major two research questions to capture the perspectives to assess the appropriateness of existing curricula in relation to labor market demands. This qualitative study integrates poetic expressions with key informant interviews to evoke deeper emotional and contextual understandings. Findings reveal that graduates perceive the curriculum as an overburden, while industry representatives highlight a significant disconnection between curricular content and actual job requirements. Similarly, TVET providers advocate for a balance between theoretical knowledge and practical application. This study stresses the urgent need for a TVET curriculum that not only aligns with labor market needs but also integrates relevant educational theories and streamlines educational processes. By addressing the concerns of diverse stakeholders through a creative lens, this research contributes to enhancing the effectiveness and relevance of TVET curricula in Nepal, thereby supporting the country’s economic growth and development.